Using Katakana Letter in Japanese Products for Customer Buying Intention - Jeremy Ivander; Dhaniar Asmarani (Journal of Japanese Language Education and Linguistics, 2022)
The Katakana letter is one of the Japanese letters, which are generally used to write foreign terms into Japanese and are also used on products to attract customers’ intention in buying a product. The researcher wants to test whether the argument is true. This research used quantitative methods, quantitative correlation approaches, and descriptive data analysis techniques to prove this argument. In collecting data, the authors surveyed to see the trend in selecting products written in Japanese characters and the reasons. After analyzing it, the main factor that attracts the customer’s attention in buying products is not the letters but rather the preference factors of the customer.